A Textual analysis tracing the development of sensitive sex and gender issues in Batibot - Ayalin, Adrian M.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
In recent years, Batibot got much attention when it aired episodes that dealt with matters such as pedophilia and sexual harassment. Sensing this, I have come up with a textual analysis of Batibot tracing how sensitive issues on sex and gender evolved within the program. Sampling of the shows analyzed was purposive. I textually analyzed three segments of the show per year using the scripts and videos available at the Batibot library. But then, being objective in this study, I have also included interviews with two child psychologists. I should say it is very necessary that I have a second opinion from the ones society value as knowledgeable in child care. With this textual analysis, I have carefully determined that Batibot broke the conservative culture of Philippine children's television -- by introdusing the radical, but unquestionably relevant issues of sex and gender in its shows.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Batibot -- Philippines -- Mass media and sex